Peran Guru Akidah Akhlak Sebagai Model Dalam Membentuk Karakter Siswa Kelas X di MA Salafiyah Wonoyoso Bumirejo Kebumen - Silvia Damayanti; Benny Kurniawan (IAINU Kebumen, 2026)
This article aims to analyze the role of Akidah Akhlak teachers as a model in shaping the character of class X students at MA Salafiyah Wonoyoso Bumirejo Kebumen as well as analyzing students' responses to the role of teachers. This research also aims to find out the most dominant character aspects formed in students. This research was carried out at MA Salafiyah Wonoyoso Bumirejo Kebumen. The research method is in the form of qualitative research. The subjects of the study include school principals, curriculum leaders, student leaders, Akidah Akhlak teachers, and students of MA Salafiyah Wonoyoso Bumirejo Kebumen. Data collection techniques use observation, interviews, and documentation. The data analysis techniques used include data collection, data reduction, data presentation, and conclusion drawn. The results of the study are: 1) The role of teachers as role models in student character education at MA Salafiyah Wonoyoso Bumirejo Kebumen provides an example of good character to students so that it should be used as a reference in behaving and doing deeds. 2) Students respond to the role of teachers as models in character formation related to the way students dress in Madrasah is appropriate although there are some that are not suitable. 3) The most dominant character aspects are formed in students through the role of teachers as models specifically, namely the character of discipline through homeroom teachers, the second is bk. in general, all teachers and employees.